Lithium ion battery electrolyte and lithium battery
By adding the first additive of a specific structural compound and other types of additives to the lithium-ion battery electrolyte, the problem of insufficient cycling performance of lithium-ion batteries under high voltage and high temperature conditions is solved, and better cycle life, power performance and high temperature cycling performance are achieved.
Patent Information
- Application Number
- CN202311769152.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-21
- Publication Date
- 2025-06-24
Smart Images

Figure CN120199891A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly to a lithium-ion battery electrolyte and a lithium battery. Background Art
[0002] Due to characteristics such as high energy density, high power density, good cycle performance, no memory effect, and environmental friendliness, lithium-ion batteries are widely used in various electronic products such as mobile communication devices like mobile phones, mobile cameras, laptops, and mobile phones, and are also strong candidates for the energy supply system of future electric vehicles. The chain organic solvents commonly used in lithium battery electrolytes include: dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, etc. and their mixtures of two or more, and the lithium salts commonly used are: lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, etc. and their mixtures of two or more. Since lithium hexafluorophosphate has the property of being easily decomposed, especially in the presence of trace amounts of water in non-aqueous electrolytes, the decomposition rate of the lithium salt will further accelerate. And the high-temperature use environment of lithium batteries will cause a significant increase in the HF content of the electrolyte, and HF will damage the SEI film on the surfaces of the positive and negative electrodes of lithium batteries, thus seriously affecting the electrochemical performance of lithium batteries.
[0003] With the expansion of the application fields of lithium batteries, especially the rapid development of electric vehicles, the market has put forward high energy density requirements for the performance of power batteries, and the energy density of single cells reached 300 wh / kg in 2020. To achieve this goal, the positive and negative electrode materials need to further improve their capacities. The positive electrode materials mainly increase the discharge capacity of the materials by increasing the nickel content and raising the charging cut-off potential. However, under high voltage conditions, the electrolyte will undergo an oxidation reaction on the surface of the positive electrode material, resulting in poor cycle performance of the material and the battery. Especially under high-temperature conditions, the oxidation reaction of the electrolyte will be further aggravated. It should be noted that for high-voltage positive electrode materials, at present, the cycle performance and high-temperature shelf performance of the battery are mainly improved by adjusting the electrolyte additives. For example, in patent CN105428719A, the organic solvent consists of a cyclic carbonate solvent, a fluorinated solvent, and a carbonate solvent, and the additive is 3-fluoro-1,3-propane sultone. The prepared electrolyte can effectively improve the cycle life and high-temperature performance of high-voltage wide-temperature lithium-ion batteries when applied to lithium-ion batteries with lithium cobaltate positive electrode materials. However, through practice, it is found that its cycle performance, especially the high-temperature cycle performance, still needs to be improved when applied to lithium-ion batteries. Summary of the Invention
[0004] The purpose of the present invention is to provide a lithium-ion battery electrolyte and a lithium battery with good cycle performance, good power performance, and low internal resistance.
[0005] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A lithium-ion battery electrolyte includes a lithium salt, an organic solvent, and an additive. The additive includes a first additive, and the first additive is selected from one or more of the compounds represented by the following general structural formula:
[0007]
[0008] Among them, R1, R2, and R3 are each independently selected from -(CH2) n -O-(CH2) m -CN, n is selected from 0 or an integer within 1 to 3, and m is selected from 0 or an integer within 1 to 5.
[0009] Preferably, n is 0, and m is selected from integers within 1 to 3.
[0010] More preferably, R1, R2, and R3 are the same.
[0011] In some embodiments, the first additive is and / or
[0012]
[0013] Preferably, the first additive accounts for 0.1 to 10% of the total mass of the electrolyte.
[0014] More preferably, the first additive accounts for 0.5 to 8% of the total mass of the electrolyte.
[0015] Even more preferably, the first additive accounts for 1 to 5.5% of the total mass of the electrolyte, such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or 5.5%.
[0016] Preferably, the additive further includes a chain nitrile compound.
[0017] In some embodiments, the chain nitrile compound is adiponitrile.
[0018] Preferably, the chain nitrile compound accounts for 0.1 to 5% of the total mass of the electrolyte.
[0019] More preferably, the chain nitrile compound accounts for 1 to 3% of the total mass of the electrolyte, such as 1%, 1.5%, 2%, 2.5%, 3%.
[0020] Preferably, the additive further includes a cyclic fluorinated carbonate additive.
[0021] In some embodiments, the cyclic fluorinated carbonate additive is fluorinated ethylene carbonate.
[0022] Preferably, the cyclic fluorinated carbonate additive accounts for 2-8% of the total mass of the electrolyte.
[0023] More preferably, the cyclic fluorinated carbonate additive accounts for 4-6% of the total mass of the electrolyte.
[0024] Preferably, the additive further includes a cyclic sulfonate additive.
[0025] In some embodiments, the cyclic sulfonate additive is 1,3-propane sultone.
[0026] Preferably, the cyclic sulfonate additive accounts for 0.1-2% of the total mass of the electrolyte.
[0027] More preferably, the cyclic sulfonate additive accounts for 0.5-1.5% of the total mass of the electrolyte.
[0028] Preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, anhydrous lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium difluoro(bis(oxalato))phosphate, 4,5-dicyano-2-trifluoromethylimidazole lithium, and lithium fluorosulfonate.
[0029] Preferably, the concentration of the lithium salt is 0.001-2 mol / L.
[0030] More preferably, the concentration of the lithium salt is 0.1-2 mol / L.
[0031] Even more preferably, the concentration of the lithium salt is 0.5-1.5 mol / L.
[0032] Preferably, the organic solvent includes carbonate and / or carboxylate.
[0033] In some embodiments, the carbonate includes one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0034] In some embodiments, the carboxylate includes one or more of ethyl propionate and propyl propionate.
[0035] The present invention also provides a lithium battery, which includes a positive electrode sheet, a negative electrode sheet, a separator, and the electrolyte as described above.
[0036] Preferably, the voltage of the lithium battery is ≥ 4.2V. When the above electrolyte is applied to a lithium battery with a voltage (≥ 4.2V), the additives in the electrolyte can form an effective and stable SEI film on the surfaces of the positive and negative electrode materials, effectively improving the cycling performance of the high-voltage lithium battery under normal temperature and high temperature conditions, suppressing the gas generation during cycling, and at the same time effectively reducing the impedance of the SEI film on the material surface and enhancing the power performance of the lithium battery.
[0037] More preferably, the voltage of the lithium battery is ≥ 4.4V.
[0038] Preferably, the active material of the positive electrode sheet is LiNi x Co y Mn (1-x-y) O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, and x + y = 1.
[0039] Preferably, the active material of the negative electrode sheet is selected from carbon materials, alloy materials, metal materials, carbon-silicon materials, carbon-silicon dioxide materials, carbon-silicon monoxide materials, carbon-tin materials, and carbon-tin oxide materials.
[0040] More preferably, the active material of the negative electrode sheet is selected from one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.
[0041] The appearance of the above lithium battery is not limited to soft package, square, cylindrical, etc.
[0042] Due to the application of the above technical solutions, the present invention has the following advantages compared with the prior art:
[0043] By adding the first additive to the electrolyte, the present invention is beneficial to improving the cycle life of the battery under high voltage and reducing the internal resistance of the battery. Specific Embodiments
[0044] The present invention will be further described below in conjunction with embodiments. However, the present invention is not limited to the following embodiments. The implementation conditions adopted in the embodiments can be further adjusted according to different requirements of specific use, and the implementation conditions not specified are the conventional conditions in the industry. The technical features involved in various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0045] Unless otherwise specified, in the specific embodiments or comparative examples of the present invention, the raw materials used are all commercially available products.
[0046]
[0047] The structural formula of additive T1 is
[0048] The structural formula of T2 is CAS No.: 1037-56-5. The preparation method of T1 is as follows: In a 500 mL three-necked flask equipped with a stirrer, a condenser and a thermometer, add 200 g of acetonitrile, 37.00 g of cyanuric chloride, and 55.00 g of 4-hydroxybutyronitrile, stir and heat up to 65 °C, add 25 g of sodium hydroxide, react at 65 °C for 4 hours, then cool down to end the reaction. Filter the reaction solution, collect the precipitated crystals, wash the crystals with water and ether twice, and after drying, obtain 51.96 g of the final product. The reaction conversion rate is 77.95%, and the purity is 99.52%.
[0049] The preparation method of T2 is as follows: In a 500 mL three-necked flask equipped with a stirrer, a condenser and a thermometer, add 200 g of acetonitrile, 37 g of cyanuric chloride, and 46 g of 3-hydroxypropionitrile, stir and heat up to 50 °C, add 25 g of sodium hydroxide, react at 50 °C for 4 hours, then cool down to end the reaction. Filter the reaction solution, collect the precipitated crystals, wash the crystals with water and ether twice, and after drying, obtain 42.6 g of 2,4,6-tricyanoethoxy-1,3,5-triazine. The purity (by liquid phase) is 99.67%.
[0050] Examples 1 to 12 and Comparative Examples 1 to 3
[0051] Battery preparation process: According to the ratio of lithium cobaltate LiCoO2: polyvinylidene fluoride (PVDF): conductive carbon SP = 95:3.5:1.5, add them to NMP (N-methylpyrrolidone) and stir evenly to form a slurry. Coat the slurry on an aluminum foil current collector on a coater, dry at 120 °C, roll, and slit to obtain a positive electrode sheet.
[0052] Using the same process, artificial graphite: sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) with a mass ratio of 95:3:2 is added to secondary water and stirred evenly to form a slurry. Coat the slurry on a copper foil current collector on a coater, dry at 120 °C, roll, and slit to obtain a negative electrode sheet.
[0053] Wind the positive electrode sheet, negative electrode sheet and PP separator into an electrode core, then put the electrode core into an aluminum-plastic film and seal the edge. After vacuum drying, inject electrolyte and seal to obtain a soft-pack polymer lithium-ion battery, abbreviated as LCO / AG.
[0054] Battery room temperature test 1: The assembled LCO / AG battery is first formed. The formation conditions are: constant current charge at 0.1C to 4.45V, and finally constant voltage charge at 4.45V for 2h, stand for 10min, and then constant current discharge at 0.2C to 3.0V. The test conditions for the high-temperature cycle performance of the lithium-ion battery are: at room temperature of 25 °C, constant current charge at 1C to 4.45V, then constant voltage charge at 4.45V for 2h, stand for 10min, constant current discharge at 1C to 3.0V, and stand for 10min.
[0055] Electrolyte preparation: Take 10% ethylene carbonate (EC), 10% propylene carbonate (PC), 30% ethyl propionate (EP), and 50% propyl propionate (PP) by weight ratio respectively. In a glove box with humidity less than 1%, mix them thoroughly to prepare an electrolyte solvent. Then, add the electrolyte salt LiPF6 with a total amount of 1 mol / L in portions. After the electrolyte salt is fully dissolved, add adiponitrile (ADN) with a content of 2 wt%, and let it stand for 24 hours to obtain the electrolyte of Comparative Example 1.
[0056] Inject the electrolyte of Comparative Example 1 into the soft-pack battery LCO / AG, and conduct tests according to Battery Normal Temperature Test Condition 1. Measure the internal resistance of the battery in the first week and record it as R; then conduct 800 cycles, and the capacity retention rate % = Capacity in the 800th week / Capacity in the first week × 100%.
[0057] For Comparative Examples 2 and 3, and Examples 1 to 12, except that the electrolyte additives vary as shown in Table 1, other electrolyte configurations and battery tests are the same as those of Comparative Example 1.
[0058] The battery performance results of Examples 1 to 12 and Comparative Examples 1 to 3 are shown in Table 1.
[0059] Table 1 Internal resistance and high-temperature cycle capacity retention rate % of Examples 1 to 12 and Comparative Examples 1 to 3
[0060]
[0061]
[0062] Among them, ADN in Table 1 represents adiponitrile, and PS represents 1,3-propanesultone.
[0063] As can be seen from Table 1, the addition of additive T1 or T2 can improve the internal resistance and normal-temperature cycle life of high-voltage batteries. And as the addition amount of additive T1 or T2 increases, the normal-temperature cycle retention rate of high-voltage batteries shows an upward trend. However, when the addition amount of additive T1 or T2 is further increased, the normal-temperature cycle retention rate of high-voltage batteries decreases and the internal resistance increases. Therefore, the addition amount of additive T1 and / or T2 is preferably 0.5 - 5.5%.
[0064] By comparing Example 1 and Example 9, Example 3 and Example 10, Example 6 and Example 11, and Example 8 and Example 12, it is found that further adding adiponitrile on the basis of adding T1 or T2 can further improve the normal-temperature cycle life of high-voltage batteries.
[0065] By comparing Example 10 and Comparative Example 2, it is found that the combined use of additive T1 or T2 and adiponitrile in this application has a better improvement effect on the internal resistance and normal-temperature cycle life of high-voltage batteries, far better than the combined use of adiponitrile and 1,3-propanesultone.
[0066] Examples 13 to 22 and Comparative Examples 4 to 5
[0067] Battery preparation process: According to LiNi 0.5 Co 0.2 Mn 0.3 O2 (abbreviation: NCM523): polyvinylidene fluoride (PVDF): conductive carbon SP = 95:3.5:1.5, added to NMP and stirred evenly to form a slurry. The slurry was coated on an aluminum foil current collector by a coater, dried at 120 °C, roll-pressed, and slit to obtain a positive electrode sheet.
[0068] Using the same process, silicon oxycarbide / carbon composite (specific capacity = 450 mAh / g, abbreviation SOC450): sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) with a mass ratio of 95:3:2 was added to secondary water and stirred evenly to form a slurry. The slurry was coated on a copper foil current collector by a coater, dried at 120 °C, roll-pressed, and slit to obtain a negative electrode sheet.
[0069] The positive electrode sheet, negative electrode sheet, and PP separator were wound into an electrode core, and then the electrode core was placed into an aluminum-plastic film and the edges were sealed. After vacuum drying, the electrolyte was injected and the package was sealed to obtain a soft-pack polymer lithium-ion battery, abbreviated as NCM523 / SOC450.
[0070] Battery high-temperature test 2: The assembled battery was first formed under the following conditions: constant current charging at 0.1C to 4.4V, and finally constant voltage charging at 4.4V for 2h, standing for 10min, and then constant current discharging at 0.2C to 3.0V. The test conditions for the high-temperature cycle performance of the lithium-ion battery at 45 °C were: under the condition of 45 °C, constant current charging at 1C to 4.4V, then constant voltage charging at 4.4V for 2h, standing for 10min, constant current discharging at 1C to 3.0V, and standing for 10min.
[0071] Electrolyte preparation: Take 20% diethyl carbonate (DEC), 30% ethylene carbonate (EC), and 50% ethyl methyl carbonate (EMC) by weight ratio respectively. In a glove box with a humidity less than 1%, they were fully mixed evenly to prepare an electrolyte solvent. Then, a total of 1 mol / L of electrolyte salt LiPF6 was added in portions. After the electrolyte salt was fully dissolved, 5wt% fluoroethylene carbonate (FEC) was added respectively, and left standing for 24 hours to obtain the electrolyte of Comparative Example 4.
[0072] The electrolyte of Comparative Example 4 was injected into the soft-pack battery NCM523 / SOC450, and tested according to the battery high-temperature test condition 2 for 500 cycles. The capacity retention rate at 500 weeks % = capacity at the 500th week / capacity at the 1st week × 100%.
[0073] Examples 13 to 22 and Comparative Examples 4 to 5 are shown in Table 2 in terms of the changes in electrolyte additives. The preparation of the electrolyte and the battery tests are the same as those in Comparative Example 4. The battery performance results of Examples 13 - 22 and Comparative Examples 3 - 4 are shown in Table 2.
[0074] Table 2 High - temperature cycle capacity retention rate % of Examples 13 - 22 and Comparative Examples 4 - 5
[0075]
[0076]
[0077] As can be seen from Table 2 above, adding T1 or T2 to the electrolyte can significantly improve the cycling performance of high - nickel ternary power batteries under high - temperature conditions. And as the addition amount of additive T1 or T2 increases, the high - temperature cycle retention rate of the battery shows an upward trend. However, as the addition amount of additive T1 or T2 further increases, the high - temperature cycle retention rate of the battery will decrease. Therefore, preferably, additive T1 and / or T2 accounts for 0.5 - 5.5% of the total mass of the electrolyte. Compared with the compounding of FEC and PS, the compounding of additive T1 or T2 of the present application and FEC has a better effect.
[0078] In addition, we also found that further adding PS to the above - mentioned electrolyte is helpful for improving the high - temperature cycling performance of the above - mentioned battery.
[0079] The above has made a detailed description of the present invention, aiming to enable those skilled in this field to understand the content of the present invention and implement it. However, it cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the protection scope of the present invention.
Claims
1. A lithium-ion battery electrolyte, comprising a lithium salt, an organic solvent and an additive, characterized in that: The additive includes a first additive, and the first additive is selected from one or more of the compounds represented by the following general structural formula: wherein, R1, R2 and R3 are each independently selected from -(CH2) n -O-(CH2) m -CN, n is selected from 0 or an integer within the range of 1 to 3, and m is selected from 0 or an integer within the range of 1 to 5.
2. The lithium-ion battery electrolyte according to claim 1, wherein: n is 0, and m is selected from integers within 1 to 3.
3. The lithium-ion battery electrolyte according to claim 2, characterized in that: R1, R2, and R3 are the same.
4. The lithium-ion battery electrolyte according to claim 3, characterized in that: The first additive is and / or 5. The electrolyte for a lithium-ion battery according to claim 1, characterized in that: The first additive accounts for 0.1 to 10% of the total mass of the electrolyte.
6. The lithium-ion battery electrolyte according to claim 1, characterized in that: The additive further includes a chain nitrile compound, and the chain nitrile compound accounts for 0.1 to 5% of the total mass of the electrolyte.
7. The electrolyte for a lithium-ion battery according to claim 1, characterized in that: The additive further includes a cyclic fluorinated carbonate additive, and the cyclic fluorinated carbonate additive accounts for 2 to 8% of the total mass of the electrolyte.
8. The electrolyte for a lithium-ion battery according to claim 1 or 7, characterized in that: The additive further includes a cyclic sulfonate additive, and the cyclic sulfonate additive accounts for 0.1 to 2% of the total mass of the electrolyte.
9. The electrolyte for a lithium-ion battery according to claim 1, wherein: The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, anhydrous lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium difluoro(bis(oxalato))phosphate, lithium 4,5-dicyano-2-trifluoromethylimidazole, and lithium fluorosulfonate; and / or, The concentration of the lithium salt is 0.001 to 2 mol / L.
10. A lithium battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The lithium battery further includes the electrolyte according to any one of claims 1 to 9.
11. The lithium battery according to claim 10, wherein: The voltage of the lithium battery is ≥ 4.2V.
12. The lithium battery according to claim 10, wherein: The active material of the positive electrode sheet is LiNi x Co y Mn (1-x-y) O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, and x + y = 1; the active material of the negative electrode sheet is selected from carbon materials, alloy materials, metal materials, carbon-silicon materials, carbon-silicon dioxide materials, carbon-silicon monoxide materials, carbon-tin materials, and carbon-tin oxide materials.
Citation Information
Patent Citations
High-voltage wide-temperature lithium ion battery electrolyte, preparation method therefor and applications
CN105428719A